La tradición de jardinería del siglo XVIII y la posibilidad de emitir juicios estéticos puros de objetos artísticos - Rojas, Ricardo (2017)
At the third section of the “Analytic of the Beautiful” of the Critique of Judgement, Kant establishes the difference between pure judgements of taste and judgements of adherent beauty. The Author contends that the definitions presented there are problematic when one attempts to reconcile them with judgements of artistic beauty. In principle, every work of art supposes certain concepts and contents that determine it as an artistic object, so it would not be possible to formulate pure judgements of taste in their regard. In order to overcome these difficulties, it becomes necessary to articulate the ideas in relation to the nature of artistic production that Kant presents in the sections on Fine Art and the Genius, where the concept of “aesthetic ideas” (understood as internal intuitions of artistic objects) is introduced. Finally, the debate on landscape and gardening in the 18th century allows us to understand how pure judgements of taste can be made from two different ways of presenting aesthetic ideas in an artistic genre.